Association of Surge Conditions with Mortality Among Critically Ill Patients with COVID-19. (April 2022) - Keene, Adam B.; Admon, Andrew J.; Brenner, Samantha K.; Gupta, Shruti; Lazarous, Deepa; Leaf, David E.; Gershengorn, Hayley B.
Objective: To determine whether surge conditions were associated with increased mortality. Design: Multicenter cohort study. Setting: U.S. ICUs participating in STOP-COVID. Patients: Consecutive adults with COVID-19 admitted to participating ICUs between March 4 and July 1, 2020. Interventions: None Measurements and Main Results: The main outcome was 28-day in-hospital mortality. To assess the association between admission to an ICU during a surge period and mortality, we used two different strategies: (1) an inverse probability weighted difference-in-differences model limited to appropriately matched surge and non-surge patients and (2) a meta-regression of 50 multivariable difference-in-differences models (each based on sets of randomly matched surge- and non-surge hospitals). In the first analysis, we considered a single surge period for the cohort (March 23 – May 6). In the second, each surge hospital had its own surge period (which was compared to the same time periods in matched non-surge hospitals). Our cohort consisted of 4342 ICU patients (average age 60.8 [sd 14.8], 63.5% men) in 53 U.S. hospitals. Of these, 13 hospitals encountered surge conditions. In analysis 1, the increase in mortality seen during surge was not statistically significant (odds ratio [95% CI]: 1.30 [0.47-3.58], p = .6). In analysis 2, surge was associated with an increased odds of death (odds ratio 1.39 [95% CI, 1.34-1.43], p < .001). Conclusions: Admission to an ICU with COVID-19 in a hospital that is experiencing surge conditions may be associated with an increased odds of death. Given the high incidence of COVID-19, such increases would translate into substantial excess mortality.